The Influence of Service Quality and Promotions to Decision Consumer Use Service Transportation on line Gojek - Norayanti Sinaga; Darma Manalu; Ridhon. MB. Simangunsong (Golden Ratio of Data in Summary, 2024)
This research aims to determine the influence of service quality and promotions on consumer decisions in using Gojek online transportation services among students at Universitas HKBP Nommensen, Medan, both partially and simultaneously. The type of research used in this research is a quantitative approach. The population in this study were all active students at Universitas HKBP Nommensen in Medan who had used the Gojek online transportation service, the exact number of which is unknown. So, using the Lemeshow formula, a sample size of 96 respondents was obtained, taken randomly to represent each faculty. Data was obtained through distributing questionnaires. The test results show that service quality has a positive and significant effect on consumer decisions, this is shown in the calculated t value of 2.966 > t table 1.98580 and a significant value of 0.004 < 0.05 . The promotion has a positive and significant effect on consumer decisions in using Gojek online transportation services, as evidenced by the calculated t value of 5.845 > t table 1.98580 and a significant value of 0.00 0 < 0.05 . Simultaneously, it was found that the quality of service and promotions had a positive and significant effect on consumer decisions using Gojek online transportation services, this was proven by the calculated F value of 78,823 ≥ F table = 3.094 and the significant value obtained was 0.000 < 0.05 . The determinant coefficient (R2) was obtained at 0.629, which means that the Consumer Decision variable can be explained by Service Quality and Promotions at 62.9% while the remaining 37.1% is explained by other variables outside Service Quality and Promotions such as Price and company reputation.